Imidazolium-Based Ionic Liquids as Stabilizers for Electrode Modification with Water-Soluble Porphyrin - Aguirre-Quintana, M; Aguirre-Quintana, M (Royal Society of Chemistry, 2019)
The water-soluble porphyrin, known as 5,10,15,20-tetrakis(1-methyl-4-pyridyl)porphyrin (TMPyP), was successfully stabilized onto a carbon paste electrode (CP) by covering up the TMPyP-modified surface with a layer of ionic liquid (IL), particularly 1-butyl-3-methyl imidazolium hexafluorophosphate (BMim PF6) or 1-butyl-3-methyl imidazolium bis(trifluoromethylsulfonyl)imide (BMim NTf2). Noncovalent interactions established between TMPyP and ILs combined with the hydrophobicity of the latter yielded a new class of modified electrodes, denoted as CP/TMPyP/IL. These new systems exhibited higher electroactive areas as compared to those of CP and CP/IL electrodes, as well as a stable and reproducible electrochemical behavior in aqueous solutions. The obtained CP/TMPyP/BMim PF6 and CP/TMPyP/BMim NTf2 electrodes were used as electrochemical sensors for nitrite oxidation. The positive results showed that these electrodes can be considered as an alternative for nitrite detection in the concentration range under investigation. © 2019 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.